PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM (STUDI EMPIRIS PADA PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BEI PERIODE 2020-2022) - Dian Esha,; Reza Maulana,; Eka Nurita,; Sekarwangi, Sekarwangi; Nofryanti, Nofryanti (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine and obtain empirical evidence of the effect of Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) on stock prices. This type of research is quantitative research that uses secondary data in the form of annual financial reports. The observation objects in this study are companies in the sub-sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The population consists of 14 companies, which were eliminated using purposive sampling techniques based on predetermined criteria, resulting in a final sample of 11 companies over a three-year period. The data analysis technique used in this study is panel data regression analysis with the help of data processing software using Eviews 12. The results show that Return On Assets (ROA) and Return On Equity (ROE) have a negative effect on stock prices, while Net Profit Margin (NPM) has a positive effect on stock prices.